Description of the S-Apple mixed rotation and transposition flap: preliminary note - Daniel Sundfeld Spiga Real; Ana Carolina Betto Castro; Helena Varago Assis (Revista Brasileira de Cirurgia Plástica, 2023)
Introduction: The flaps, whose function is to reduce or redirect tension during a closure, are classified based on their primary movement: transposition, advancement, and rotation, each with its characteristics, indications, and peculiarities. Combining the qualities of the transposition flaps with those of rotation, which make up the S-Apple flap, makes it more versatile and with better aesthetic results than the bilobed flap, which denotes the archetype for the appearance of the S-Apple. Method: Having the rotation and transposition flaps as an archetype, four flaps are made in the S-Apple flap, which are rotated and transposed to close the defect. This is excised in a circular format for the oncological safety of margins. The “S” of the flap is traced at a 30° angle in relation to the defect. The arm dimension must be the same diameter as the defect, with the flaps transposed as in a z-plasty, and the flap rotated to cover the defect, resulting from the exeresis of the lesion. Results: No necrosis, infection, dehiscence, recurrences, trapdoor scars, or rotation point elevation were observed. The scars were classified as satisfactory and extremely satisfactory. Conclusion: The S-Apple flap proved versatile and easy to mark with excellent aesthetic and functional results.